Proceedings of the 24th Conference on Formal Methods in Computer-Aided Design – FMCAD 2024 (TU Wien Academic Press, 2024)
The Conference on Formal Methods in Computer-Aided Design (FMCAD) is an annual conference on the theory and applications of formal methods in hardware and system in academia and industry for presenting and discussing groundbreaking methods, technologies, theoretical results, and tools for reasoning formally about computing systems. FMCAD covers formal aspects of computer-aided system testing.